1998
DOI: 10.1093/humrep/13.9.2521
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural pathology of the sperm flagellum: association between flagellar pathology and fertility prognosis in severely asthenozoospermic men

Abstract: An ultrastructural study of spermatozoa in a series of 247 severely asthenozoospermic patients disclosed two kinds of anomalies. The first was dysplasia of the fibrous sheath, a primary defect of spermatozoa with hypertrophy and hyperplasia of the fibrous sheath, associated axonemal anomalies, familial incidence and chronic respiratory disease. The patients could be divided into two subgroups: the complete form (all spermatozoa affected) and the incomplete form (alterations in 70-80% spermatozoa). There were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(29 citation statements)
references
References 13 publications
0
27
0
2
Order By: Relevance
“…The diameter of the human sperm tail varies from 400 to 880 nm, according to the literature (Chemes and Rawe, 2003; Chemes et al, 1998; Serres et al, 1983). This wide range of reported values is likely due to the differences in sample preparation methods, such as sample dehydration, required for electron microscopy, which often distorts the original sample size.…”
Section: Resultsmentioning
confidence: 99%
“…The diameter of the human sperm tail varies from 400 to 880 nm, according to the literature (Chemes and Rawe, 2003; Chemes et al, 1998; Serres et al, 1983). This wide range of reported values is likely due to the differences in sample preparation methods, such as sample dehydration, required for electron microscopy, which often distorts the original sample size.…”
Section: Resultsmentioning
confidence: 99%
“…The genotypic sperm defect DFS (dysplasia of the fibrous sheath) (Chemes et al. , 1987, 1998), associated with respiratory pathology and familial inheritance, is characterized by different distortions in the fibrous sheath, microtubular doublets and mitochondrial sheath, all arranged in a short and thick tail.…”
Section: Mitochondrial Energy Metabolism In Human Spermmentioning
confidence: 99%
“…Asthenozoospermia (AS), defined as low-motile spermatozoa in the ejaculate, is a frequent cause of human male infertility (Chemes et al 1998). It is reported that more than 80% of the spermatozoa from infertile patients had motility defects and 19% of them were diagnosed with AS (Curi et al 2003).…”
Section: Introductionmentioning
confidence: 99%